2019
DOI: 10.1101/647586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Ictal Recruitment of Midline Thalamus in Mesial Temporal Lobe Epilepsy

Abstract: word count -100 Running head-38 characters Manuscript -Introduction word count-239 Discussion word count -264 Complete manuscript word count-1369 References-18 AbstractThe causal role of midline thalamus in the initiation and early organization of mesial temporal lobe seizures is studied. Three patients undergoing stereoelectroencephalography were enrolled for the placement of an additional depth electrode targeting the midline thalamus. The midline thalamus was recruited in all three patients at varying point… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The overall complication rates are low and comparable to electrodes placed in any other location. With these results, we propose that if patients are fully informed of the risks involved, there are significant benefits of obtaining robust signals from thalamic nuclei involved in seizure networks which may help guide future therapies 26,27,29 . Some of the early studies by our group have shown (1) the periictal electrophysiological changes occurring in the thalamus during the seizures, (2) the cortical responsiveness to thalamic…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…The overall complication rates are low and comparable to electrodes placed in any other location. With these results, we propose that if patients are fully informed of the risks involved, there are significant benefits of obtaining robust signals from thalamic nuclei involved in seizure networks which may help guide future therapies 26,27,29 . Some of the early studies by our group have shown (1) the periictal electrophysiological changes occurring in the thalamus during the seizures, (2) the cortical responsiveness to thalamic…”
Section: Figurementioning
confidence: 98%
“…However, the local field potentials (LFPs) of the thalamus were of a lower amplitude compared to the cortical LFPs ( Fig 6). The electrophysiological data thus obtained has been analyzed and published previously addressing key clinical questions 26,27,29,41 .…”
Section: Table 1 Seeg Implantation and Complicationsmentioning
confidence: 99%
“…Experimental studies suggest that the thalamic nuclei play diverse roles in initiation, propagation, and termination (collectively termed as ictogenesis) of limbic seizures (Bertram et al, 2001;Takebayashi et al, 2007;Langlois et al, 2010;Feng et al, 2017). In TLE, prior clinical studies have explored the influence of lateral and medial thalamic nuclei in ictogenesis, but none to date have studied the anterior nucleus of the thalamus (ANT) -a node that is integral to the limbic network (Child and Benarroch, 2013;Evangelista et al, 2015;Romeo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%